Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/om800597f
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Calcium and Zinc Complexes with Bridged β-Diketiminate Ligands: Investigations on Epoxide/CO2 Copolymerization

Abstract: A series of dinucleating bis(β-diketiminate) ligands with rigid bridges has been prepared. In all cases the β-diketiminate unit is 2,6-iPr2C6H3NC(Me)C(H)C(Me)N-(bridge), and the bridges are either para-phenylene, meta-phenylene or 2, 6-pyridylene (the dinucleating ligands are abbreviated as PARA-H2, META-H2 and PYR-H2, respectively). These ligands have been converted to heteroleptic bimetallic calcium and zinc complexes. For calcium, only the PARA-phenylene bridged ligand led to a heteroleptic bimetallic calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
84
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 35 publications
2
84
0
3
Order By: Relevance
“…Limberg, Hultzsch and co-workers as well as Harder and co-workers focussed on a BDI-like structure in their dinuclear catalysts 6 and 7. [37,38] Recently we proofed the bimetallic nature of the copolymerisation of propylene oxide and carbon dioxide with dimeric salphen complexes (Scheme 4). [11,39,40] All of these catalysts finally led to the homogeneous dinuclear zinc catalyst reported by Williams et al, which is active in the copolymerisation of cyclohexene oxide and carbon dioxide even at one atmosphere of CO 2 and therefore shows the highest turnover frequency (TOF) ever reported under such conditions (25 h À1 ; Scheme 4).…”
mentioning
confidence: 93%
“…Limberg, Hultzsch and co-workers as well as Harder and co-workers focussed on a BDI-like structure in their dinuclear catalysts 6 and 7. [37,38] Recently we proofed the bimetallic nature of the copolymerisation of propylene oxide and carbon dioxide with dimeric salphen complexes (Scheme 4). [11,39,40] All of these catalysts finally led to the homogeneous dinuclear zinc catalyst reported by Williams et al, which is active in the copolymerisation of cyclohexene oxide and carbon dioxide even at one atmosphere of CO 2 and therefore shows the highest turnover frequency (TOF) ever reported under such conditions (25 h À1 ; Scheme 4).…”
mentioning
confidence: 93%
“…However, most of the reported structures suffer from poor solubility or low polymerization activity. [16,[22][23][24][25][26][27][28][29][30] One major breakthrough aside from zinc phenoxides developed by Darensbourg is the synthesis of b-diketiminato (BDI) zinc complexes by Coates et al [21,[31][32][33][34][35][36][37][38][39][40][41] For these highly active catalysts the mechanism involving a dimetallic intermediate was unambiguously demonstrated. Kinetic investigations using in situ IR spectroscopy showed that the rate-determining step is the ring opening of the epoxide.…”
mentioning
confidence: 99%
“…X-ray crystallography was recorded using the Agilent Xcalibur 3 E and PX Ultra A X-ray Diffraction Systems with Cu Single Wavelength Sealed Tube Source with wavelengths of 0.71 Å and 1.54 Å and at 173 K. The dinucleating ligands 1•H2 and 2•H2 were prepared by modification of the literature procedures (see supporting information). [37][38][39] The copper cluster [2•Cu2]2 was prepared by the literature procedure. 31 Synthesis of 3•H2: To a solution of 2-(2,6-di-iso-propylphenyl)imido-2-penten-4-one (2.6 g, 9.98 mmol) in DCM (15 mL) at room temperature was added a solution of [Et3O]BF4 (2.1 g, 11.03 mmol) in DCM (5 mL) to produce a brown-colored solution.…”
Section: Methodsmentioning
confidence: 99%